Vertebral Artery Variation in Patients With Congenital Cervical Scoliosis: An Anatomical Study Based on Radiological Findings. Issue 4 (15th February 2021) - Xia, Tian; Sun, Yu; Wang, Shaobo; Zhang, Fengshan; Zhang, Li; Pan, Shengfa; Diao, Yinze; Chen, Xin; Zhou, Feifei; Zhao, Yanbin
Abstract : Study Design: Observational, anatomical, radiological study. Objective: The aim of this study was to explore the incidence and type of vertebral artery (VA) variation in patients with congenital cervical scoliosis and approach their clinical importance during surgery. Summary of Background Data: Congenital scoliosis of the cervical spine is usually sporadic and caused by a variety of bone structural anomalies. Most of the cases remain asymptomatic. Surgical intervention is the main management for patients with neurological compromise or with cosmetic demands. The operation involved more screw insertion and osteotomy than the regular degenerative cases. The incidence and pattern of VA variants in these patients have not been reported. Methods: Patients with congenital cervical scoliosis treated in our department were reviewed. We measured Cobb angle of cervical spine. We observed bilateral VAs and recorded variants. We measured their diameter in each segment through CT angiography. The bilateral diameter in each patient was then compared respectively. Result: There is a total of 44 patients enrolled. The incidence of VA variation was 41% (18/44). Fifty percent (22/44) of patients had the dominant VA with no difference between concave side and convex side. Patients with a dominant VA had a larger Cobb angle than those who had not (30.25° vs. 23.24°, P < 0.05). The courses of VA were abnormal in 18 patients. Two patients had unilateral variant in V1 segment. Twelve patients had variants in V2 segment. Eight patients had variants in V3 segment. Three patients had VA variants in multiple sites. Conclusion: In patients with congenital cervical scoliosis, the dominance of VA is not related to the convex side or concave side, but patients with a dominance of VA have a larger Cobb angle. The incidence of variant in V2 and V3 segment is higher. A thorough evaluation of bilateral VAs is required before surgery. Extra cautions must be taken during surgery. Level of Evidence: 5 Abstract : This study aims to explore the incidence and pattern of vertebral artery (VA) variant in patients with congenital cervical scoliosis. Forty-four patients enrolled in this research. The incidence of VA variation was 41%, mainly located in V2 and V3 segment.